Genetic burden linked to founder effects in Saguenay–Lac-Saint-Jean illustrates the importance of genetic screening test availability. Issue 10 (28th April 2021) - Bchetnia, Mbarka; Bouchard, Luigi; Mathieu, Jean; Campeau, Philippe M; Morin, Charles; Brisson, Diane; Laberge, Anne-Marie; Vézina, Hélène; Gaudet, Daniel; Laprise, Catherine
Abstract : The Saguenay–Lac-Saint-Jean (SLSJ) region located in the province of Quebec was settled in the 19th century by pioneers issued from successive migration waves starting in France in the 17th century and continuing within Quebec until the beginning of the 20th century. The genetic structure of the SLSJ population is considered to be the product of a triple founder effect and is characterised by a higher prevalence of some rare genetic diseases. Several studies were performed to elucidate the historical, demographic and genetic background of current SLSJ inhabitants to assess the origins of these rare disorders and their distribution in the population. Thanks to the development of new sequencing technologies, the genes and the variants responsible for the most prevalent conditions were identified. Combined with other resources such as the BALSAC population database, identifying the causal genes and the pathogenic variants allowed to assess the impacts of some of these founder mutations on the population health and to design precision medicine public health strategies based on carrier testing. Furthermore, it stimulated the establishment of many public programmes. We report here a review and an update of a subset of inherited disorders and founder mutations in the SLSJ region. Data were collected from published scientific sources. This work expands the knowledge about the current frequencies of these rare disorders, the frequencies of other rare genetic diseases in this population, the relevance of the carrier tests offered to the population, as well as the current available treatments and research about future therapeutic avenues for these inherited disorders.